2014
DOI: 10.1111/clr.12328
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐implant soft tissue and marginal bone adaptation on implant with non‐matching healing abutments: micro‐CT analysis

Abstract: The dimension of the horizontal offset would play a minimal role in reducing bone remodeling, whereas the configuration of the transmucosal component would directly influence marginal bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 14 publications
4
24
0
Order By: Relevance
“…In the current study, we observed significant differences in the amount of bone remodeling above the implant platform between the two groups. This finding is in agreement with the animal studies from Finelle et al () and Souza et al (). In both studies, healing abutments with different diameters and emergence profiles were used.…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we observed significant differences in the amount of bone remodeling above the implant platform between the two groups. This finding is in agreement with the animal studies from Finelle et al () and Souza et al (). In both studies, healing abutments with different diameters and emergence profiles were used.…”
Section: Discussionsupporting
confidence: 94%
“…Berberi et al (2014) described the placement of healing abutments at the moment of implant placement in fresh extraction sockets, thereby reducing marginal bone loss (Berberi et al 2014). However, this outcome disagrees with a study by Koutouzis et al (2013), which found that implants receiving a final abutment at the time of implant placement exhibited minimal marginal bone loss, with similar results to implants subjected to twicerepeated abutment disconnection and reconnection (Koutouzis et al 2013;Finelle et al 2014). In other research, the topography of healing abutments of 2 mm in height on implants placed 1 mm subcrestally had no influence on soft tissues and did not increase inflammation around the implant-abutment interface (Zitzmann et al 2002;Huang et al 2014).…”
Section: Discussionmentioning
confidence: 57%
“…(), which found that implants receiving a final abutment at the time of implant placement exhibited minimal marginal bone loss, with similar results to implants subjected to twice‐repeated abutment disconnection and reconnection (Koutouzis et al. ; Finelle et al ). In other research, the topography of healing abutments of 2 mm in height on implants placed 1 mm subcrestally had no influence on soft tissues and did not increase inflammation around the implant–abutment interface (Zitzmann et al.…”
Section: Discussionmentioning
confidence: 77%
“…The influence of abutment morphology (and the abutment's surface treatment) on bone remodeling during the osseointegration period has also been investigated (Finelle et al. ; López‐López et al. ).…”
mentioning
confidence: 99%
“…Various studies have shown the long-term viability of this non-submerged technique (Weber et al 2000;Mericske-Stern et al 2001;Cochran et al 2011). The influence of abutment morphology (and the abutment's surface treatment) on bone remodeling during the osseointegration period has also been investigated (Finelle et al 2015;L opez-L opez et al 2016). But few studies have made a direct comparison between submerged and non-submerged protocols during the osseointegration period (Zitzmann et al 2002).…”
mentioning
confidence: 99%